Modulation of immunogenicity and Epstein-Barr virus gene expression in lymphomas with small-molecule inhibitors - Cheuk, Fabian Jia Jun (Nanyang Technological University, 2023)
Natural killer/T-cell lymphoma (NKTL) is an Epstein-Barr virus (EBV)-associated lymphoproliferative disorder characterized by poor clinical outcomes. With its restricted latent gene expression, the therapeutic efficiency of cytotoxic T lymphocytes (CTL) immunotherapy is limited. We investigated the use of small molecule inhibitors decitabine, a DNA hypomethylating agent, and acyclovir, an inhibitor of viral DNA polymerase. We hypothesized they can augment EBV gene expression to not only potentiate CTL immunotherapy, but also induce gene expression profiles associated with longer progression-free survival (PFS) periods in NKTL patients. We treated NKYS and NKS1 cell lines with both small-molecule inhibitors and subjected them to immunoblotting and real-time quantitative polymerase chain reaction. We found that the cotreatment enhanced latent membrane protein 1 (LMP1) expression and inhibited late lytic gene expression, recapitulating long-PFS state. We then validated the enhanced immunogenicity of decitabine-treated NKS1 cells with T-cell receptor mimic antibodies and demonstrated enhanced human leukocyte antigen expression and LMP1/2 epitopes presentation. Surprisingly, LMP1/2 epitopes showed different magnitude of presentation. Cell proliferation and viability assays showed that the long-PFS state induced by decitabine and acyclovir exhibited reduced proliferative capacity and viability. These results suggest additive effects of decitabine and acyclovir in NKTL and have potential as adjuvants in immunotherapeutic regimens.